Upaya Meningkatkan Kemampuan Menulis Cerita Pendek Melalui Media Gambar Seri - Rahayuningsih, Lola; Putrini R Harahap, Saima (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
This research was carried out based on the obstacles found by observers and teachers in the classroom. The obstacle faced is the low skill in writing short stories. Teachers can improve students' writing skills and be able to express ideas in written form by utilizing supporting media, namely using series of images as media. In this study, implementation steps were carried out using tests or evaluation results at the end of the learning meeting. This research was conducted with the aim of finding out whether there was an improvement in students' writing skills by using series of picture media for students. Class IV students at SDN 7 Praya, with a total of 22 students, were the study subjects. This research was carried out using 2 cycles. The student's standard score in phase I was 70.5 and in phase II it was 85 with the specified indicator of success being 75. The students who succeeded in achieving the score determined in phase I were 14 students and those who did not succeed were 8 people, in phase II all participants students succeed in achieving grades. From the results obtained in phase I and phase II, namely 70.5 to 85, there was an increase of 15%. So it can be said that in the teaching and learning process there has been quite a significant improvement so that this research can be concluded as successful. From the results of the implementation of the improvements made, it can be concluded that using series of picture media in Indonesian language learning is very effective in improving students' writing skills.